Percutaneous laser microdiscectomy at cervical neurocompressive discogenic syndromes (analytic review) - Yu. E. Pedachenko (Ukrainian Neurosurgical Journal, 2007)
Actual problem of new miniinvasive method application for cervical discogenic syndromes surgical treatment — percutaneous laser microdiscectomy is described. Experience of microdecompressive method use is represented (based on the literature data).The main attention is paid to comparative analysis of percutaneous laser microdiscectomy at cervical discogenic neurocompressive syndromes, and possible complications. Directions of problem further study, first of all effectiveness of microdecompressive method at different cervical neurocompressive discogenic syndromes, and dependence of prognosis on one- or multilevel affection.